Is Vagus Nerve Therapy a Potential Alzheimer's Disease Treatment? - Isea Raul (International Journal of Global Health, 2023)
A potential treatment for Alzheimer's disease is vagus nerve therapy, which has been made possible by considerable advances in neuroscience. An essential component of the autonomic nervous system, the vagus nerve regulates memory, inflammation, and cognition. Researchers hope to delay the progression of Alzheimer's disease and improve cognitive function by implanting a vagus nerve stimulator (VNS). Alzheimer's patients have higher heart rate variability, according to an ECG study, which may be advantageous. To completely grasp its mechanics and long-term effectiveness, more research is necessary.
Keywords: Alzheimer